Economic thinking in Latin America (1950- 2010). Background and perspectives - Barón, Diego Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This research deepens on history and prospects of Economic Thinking in Latin America between 1950 and 2010. We identify economic thinking, the main tenets and historical contexts of the Economic Commission for Latin America -ECLAC and the Latinamerican structuralism, based on the work of Prebisch 1949, neostructuralism of Fanjzilber, and the theory of dependency of Cardoso and Faletto. We describe the economic integration in Latin America, its postulates and sources of economic thinking, and propose that the Union of South American Nations and the Bolivarian Alternative for the Americas -People´s Trade Agreement-, incorporate ideas that transform economic thinking.